(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Any illegal behavior involving a computer, a device on the network, or a network is considered a cybercrime. Whereas most cybercrimes are committed to making money for the perpetrators, certain cybercrimes are committed against computers and other devices immediately to harm or destroy them. The susceptibility of e-businesses to cybercrime is a serious issue. Cybercrime refers to any illegal conduct carried out online, including spoofing, phishing, botnet, or denial-of-service assaults that result in financial losses for e-commerce businesses. This paper gives instances of several businesses that have been impacted by typical cybercrimes and illustrates how they are committed. Additionally, some advice on crime prevention is provided. Internal auditors would benefit from knowing the different forms of cybercrime as well as the fundamental preventive methods since they may assess if a business has effective cybercrime defenses. In this paper, the author talks about cybercrimes, types of cybercrimes, and preventive measures. In the future, this paper will aware of cybercrimes or preventive steps.